The Impact of Cooperative Learning on Iranian Intermediate EFL Learners’ Reading Comprehension: The Case of Jigsaw Technique - Behnaz Raji (Universitas Sembilanbelas November Kolaka, 2020)
This study examined the effect of Jigsaw technique as a part of cooperative learning on Iranian EFL learners’ reading comprehension. To this end, 40 intermediate participants were selected out of 73 EFL learners based on the results of Oxford Quick Placement Test (OQPT). The participants were divided into two groups; control and experimental. Then, the participants of both groups were pretested on reading comprehension. After pre-testing, the cooperative learning activities (Jigsaw technique) were practiced with the participants of the experimental group during 5 sessions. The experimental participants were assigned to five-member teams to work on reading texts. Each team member read an assigned section and then members from different teams who had studied the same sections met in ‘expert groups’ to discuss their sections. Then, students returned to their own teams and taught their team-mates about their section. On the other hand, the control group received traditional teacher-fronted instruction throughout the classroom time. After the treatment sessions, a teacher-made reading comprehension post-test was given to the participants of both groups to measure their reading comprehension ability after the treatment. The results of paired samples t-test and independent samples t-test revealed that the experimental group outperformed the control group on the post-test. The findings also showed that there was a significant difference between the post-tests of both groups in favor of the experimental group.